Evaluating E-Module KPSP: A Research and Development Approach - Neli Sunarni; Aulia Ridla Fauzi; Resna Litasari (Inspirasi Foundation, 2023)
Introduction: Media and learning resources are part of the components that influence learning. Utilizing and empowering e-modules to support learning is necessary, not only to increase the effectiveness and quality of education but, more importantly, to improve mastery of the material for both lecturers and students. Objective: The purpose of this research is to design learning media in the form of KPSP e-modules, which are used to support the learning process so as to increase student attractiveness and student understanding. Method: This study uses a research and development (R&D) procedure. The subjects of this study were 58 Midwifery Diploma students for the 2021–2022 academic year. Result: The content aspect of the KPSP e-module is rated as